Nutrition Plate as a Nutritional Media to Increase Knowledge of Balanced Nutrition for Mothers with Toddlers in Muara Gembong - Titis Nurwulan Suciati; Moh. Rifaldi Akbar; Lukman Azis; Dendra Arif Fadillah; Dwicky Nurrochman Susanto; Saphira Dea Caroline (Jurnal Sinergitas PKM & CSR, 2023)
This community empowerment is carried out by the communication science academia from Universitas Bhayangkara Jakarta Raya. This community empowerment is assisted by a food technology lecturer from Universitas Al Azhar Indonesia. This community empowerment seeks to increase the knowledge of mothers with a toddler about balanced food and nutrition. This community empowerment is carried out in the Desa Pantai Bakti, Muara Gembong, one of the districts with the highest level of under-five malnutrition in Indonesia. There are two methods (mix-method approach) this community empowerment use in this activity: focus group discussion and experimental method. These two approaches aim to measure intervention (counseling, pamphlet installation, and nutritional plate medium). This community empowerment uses pre-test and post-test for the same group to measure changes in subject knowledge before and after counseling (intervention). This community empowerment affects changes in subject knowledge (n=15). The mother's knowledge about balanced nutrition was statistically significantly increased by two-tail P(T£ t) 0.002788939 with Sig. £ a 0,05.